Antiproliferative prostaglandins activate heat shock transcription factor. - Amici, C (1992)
Treatment of human K562 erythroleukemia cells with the antiproliferative prostaglandin A1 results in the elevated transcription of two heat shock genes, HSP70 and HSP90. Parallel with increased heat shock gene transcription is the activation of heat shock transcription factor. Heat shock transcription factor levels are induced within 60 min after prostaglandin A1 addition to levels similar to that achieved during heat shock. The requirement for protein synthesis for prostaglandin A1 activation of heat shock transcription factor suggests that effects on nascent protein synthesis may be involved in the signaling mechanism. Although it is unclear whether the activation of a heat shock response by prostaglandins is relevant to the biochemical properties of these natural substances, cells pretreated with prostaglandin A1 are protected against a subsequent heat shock, indicative of a thermotolerant state.